Bony Protuberances on the Anterior and Posterior Clinoid Processes Lead to Traumatic Internal Carotid Artery Aneurysm Following Craniofacial Injury - Cheong, Jin Hwan (The Korean Neurosurgical Society, 2011)
Traumatic intracranial aneurysms are rare, comprising 1% or less of all cerebral aneurysms. The majority of these aneurysms arise at the skull base or in the distal anterior and middle cerebral arteries or their branches following direct mural injury or acceleration-induced shearing force. We present a 50-year-old patient in whom subarachnoid hemorrhage (SAH) was developed as a result of traumatic aneurysm rupture after a closed craniofacial injury. Through careful evaluation of the three-dimensional computed tomography and conventional angiographies, the possible mechanism of the traumatic internal carotid artery trunk aneurysm is correlated with a hit injury by the bony protuberances on the anterior and posterior clinoid processes. This traumatic aneurysm was successfully obliterated with clipping and wrapping technique. The possibility of a traumatic intracranial aneurysm should be considered when patient with SAH demonstrates bony protuberances on the clinoid process as a traumatic aneurysm may result from mechanical injury by the sharp bony edges.